2014
DOI: 10.1371/journal.pone.0093132
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Specific Mortality in Insulin-Treated Type 2 Diabetes Patients

Abstract: AimsTo test the hypothesis that cumulative exposure to insulin and long-acting insulin analogs might be associated with cancer mortality in diabetes patients.MethodsAll consecutive diabetes patients aged over 40 years, residing in a major urban area were screened at their first diabetes outpatient visit between 01/01/2001-12/31/2008 (n = 79869). Exclusion criteria were insulin treatment at screening, no insulin treatment until 12/31/2008, less than 6 months of glucose-lowering treatment alone before insulin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…This has been confirmed by other several large studies [147][148][149]. In particular, the use of glargine was not associated with either an increased mortality for cancer [147] or a higher incidence of malignancies [148,149].…”
Section: Abnormalities Of Gh/igf-1 Axis In Diabetes Mellitus: Clinicasupporting
confidence: 80%
See 1 more Smart Citation
“…This has been confirmed by other several large studies [147][148][149]. In particular, the use of glargine was not associated with either an increased mortality for cancer [147] or a higher incidence of malignancies [148,149].…”
Section: Abnormalities Of Gh/igf-1 Axis In Diabetes Mellitus: Clinicasupporting
confidence: 80%
“…Really, several subsequent clinical studies did not confirm these data, and a specific large randomized controlled trial, designed to test cardiovascular and cancer risk of glargine, did not show any increase in cancer risk in patients treated with glargine [146]. This has been confirmed by other several large studies [147][148][149]. In particular, the use of glargine was not associated with either an increased mortality for cancer [147] or a higher incidence of malignancies [148,149].…”
Section: Abnormalities Of Gh/igf-1 Axis In Diabetes Mellitus: Clinicamentioning
confidence: 95%
“…Large cell histology has also been reported to be associated with worse survival compared to other histologic types (12, 14). The associations between type II diabetes mellitus and high risk of mortality in lung cancer patients have been reported in previous studies 3033 although the association was not consistently observed in other studies 34 . Peripheral vascular and cerebrovascular diseases are among the most commonly found comorbidities among lung cancer patients that contributed to decreased survival in NSCLC patients 35, 36 .…”
Section: Discussionmentioning
confidence: 72%
“…Other publications demonstrated that insulin treatment did not influence breast cancer survival significantly . One study even reported that insulin treatment was a favourable factor for breast cancer patients . In summary, there was large variation in the abovementioned studies, and the effect of insulin therapy on the prognosis of breast cancer is still a mystery.…”
Section: Introductionmentioning
confidence: 99%